Analisis Pengaruh Getaran Pompa Terhadap Aliran Fluida pada Proses Pemipaan Skala Laboratorium - I Gede Eka Lesmana; Febriani Chairunisa; Maria Putri Hartanto; Rovida Camalia Hartantrie (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2022)
Piping installations are generally used to drain fluids with the help of tools such as pumps. The pump motor causes a high enough vibration so that if it is connected to a piping installation it can cause vibrations in the pipe. If the vibration generated by the pump against the pipe is strong enough, it can cause problems such as misalignment, and others. To identify the resulting vibration. In this study, using variations in the diameter of the pipe and variations in the distance of the blockage in the clogged pipe. Variations in the diameter of the pipes used are ½”, ¾”, 1”, 1 ¼”, dan 1 ½”. And the variation of the distance of the blockage on the pipe that is plugged is 196.5 cm, 206.5 cm, 216.5 cm, 226.5 cm, and 236.5 cm. The comparison of the value of the vibration velocity becomes a reference to determine the diameter of the pipe that is suitable for installation and to find out that the clogged pipe can flow fluid. Based on the results of this study, a pipe with a diameter of ½”has the highest vibration velocity value of 6.1 mm/s and a pipe with a diameter of 1 ½” has the lowest vibration velocity value of 0.82 mm/s and in the condition of a clogged pipe the value is 1, 04 mm/s and the average value of the vibration velocity in the pipe under normal conditions is 0.7 mm/s.